IDENTIFIKASI KAPASITAS KELEMBAGAAN LOKAL DALAM PENATAAN KAWASAN KUMUH PERKOTAAN (Studi kasus: Kelurahan Purwosari, Kecamatan Mijen, Kota Semarang) - Hendrianto Sundaro (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
This research reveals the role of local institutions in the slum upgrading progam through the BKM Bangkit Sejahtera, management units and self-help groups (KSM). Through these local institutions, people are involved in the National Slum Upgrading Program (NSUP). This research aims to identify the capacity of local institutions in the slums upgrading. The method used in this research is a mixed method with a case study approach. The sample used was from the BKM Bangkit Sejahtera element and its management units as well as the Community Self-Help Group (KSM) with the purposive sampling technique. Data obtained through questionnaires, observation and interviews. The analysis technique was carried out with a descriptive statistical approach and SWOT analysis with space matrix model. The results of the analysis indicate that there are several potential and problems local institutional capacity. The conclusion of this research is local institutional capacity degree in slum upgrading program is identified as Quadrant III: Competitive, which means that although there are several of internal weaknesses but there are several of external opportunities that can be optimized to strengthen local institutional capacity so that it can provide a more significant contribution in various development and community activities, especially the slum upgrading. The suggestion from the results of this research is necessary to formulate a program indication of capacity building by referring to the capacity development strategy with the SWOT approach that was carried out in this research.